1999
DOI: 10.1080/09603129973056
|View full text |Cite
|
Sign up to set email alerts
|

Levels of cadmium, copper and iron in deciduous teeth of children living in Bahrain

Abstract: Shed deciduous teeth were collected from children (n = 61) living in the island of the State of Bahrain. The teeth were analyzed for the toxic cadmium metal and for the biologically essential metals iron and copper. The m ean concentrations of cadmium, iron and copper were 53.8 ng/g, 20.22 m g/g and 2.78 m g/g respectively. The data obtained showed no clear relation between the trace metal concentrations and the children's age, sex, social status or nationality. Teeth from the upper jaw were found to have high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
8
2
Order By: Relevance
“…Previous studies showed that the concentrations of metals in deciduous teeth vary with physiological and environmental factors (Al-Haddad et al 1999;Barton 2011;Bayo et al 2001;Begerow et al 1994;Blanusa et al 1990;Ewers et al 1990;Fishcher et al 2009;Frank et al 1999;Gierat-Kucharzewska et al 2003;Gomes et al 2004;Kristjansson et al 2000;Orzechowska-Wylegala et al 2011;Tvinnereim et al 1997Tvinnereim et al , 1999Tvinnereim et al , 2000. Teeth are considered the best bioindicators for tracing elements; human deciduous teeth are easily available biological materials and have been used to evaluate nutritional, physiological, and environmental factors affecting the concentrations of trace metals in human.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous studies showed that the concentrations of metals in deciduous teeth vary with physiological and environmental factors (Al-Haddad et al 1999;Barton 2011;Bayo et al 2001;Begerow et al 1994;Blanusa et al 1990;Ewers et al 1990;Fishcher et al 2009;Frank et al 1999;Gierat-Kucharzewska et al 2003;Gomes et al 2004;Kristjansson et al 2000;Orzechowska-Wylegala et al 2011;Tvinnereim et al 1997Tvinnereim et al , 1999Tvinnereim et al , 2000. Teeth are considered the best bioindicators for tracing elements; human deciduous teeth are easily available biological materials and have been used to evaluate nutritional, physiological, and environmental factors affecting the concentrations of trace metals in human.…”
Section: Resultsmentioning
confidence: 98%
“…Komarnicki (2000) investigated the level of lead and cadmium in several organs of moles and found that both metals accumulate in bone tissue with increasing age. AlHaddad investigated the concentrations of Fe, Cu and Pb in children aged between 6 and 15 years and found that no clear relation between trace metal concentrations and the children's age (Al-Haddad et al 1999). Bayo et al (2001) investigated the level of Pb and Cd in children aged between 4 and 11 and found that the concentrations of both metals decreased significantly with children's age.…”
Section: Agementioning
confidence: 96%
See 3 more Smart Citations